Caracterização da mastofauna terrestre em paisagem remanescente de Floresta Estacional Semidecidual no Centro de Ciências Agrárias (CCA – UFSCar), Araras – SP. - Rossi, Inara Augusto (Universidade Federal de São Carlos, 2024)
In the current context, coexistence with climate, water and biodiversity crises is imminent, arising from the unbalanced relationship with nature. In this sense, the continuous degradation of forest remnants in the Atlantic Forest, a biome considered one of the world's biodiversity hotspots, constitutes one of the greatest threats to mammals present in the biome. The degree of threat and the ecological importance of the group highlight the need to include information in environmental diagnoses. Distribution data is very important for assessing conservation status. Therefore, it is essential to carry out studies to characterize mammals in anthropic environments, making it possible to understand the impacts that agricultural crops, forest fragmentation and environmental factors can have on the local mammal fauna. The present study aimed to characterize the terrestrial mammal fauna present in a modified landscape formed by an agricultural matrix, permanent preservation areas and a remnant of Semideciduous Seasonal Forest, evaluating its richness, constancy and composition. The study was carried out at the Agricultural Sciences Center, UFSCar campus, located in the municipality of Araras in the interior of the State of São Paulo. Two plant formations were monitored: an area in the process of restoration in APP and a remnant of Semideciduous Seasonal Forest. The records were carried out from January 2017 to October 2023, with the exception of 2019, using the photographic trapping method. Total wealth was estimated using the Jackknife 1 estimator and constancy was calculated according to Dajoz. 17 species of land mammals were recorded, distributed across six orders: Artiodactyla, Carnivora, Cingulata, Didelphimorphia, Lagomorpha and Rodentia. A total of 21 species were estimated for the area, using Jackknife 1. The most constant and frequent species are Hydrochoerus hydrochaeris (51.91%) and Cerdocyon Thous ands (21.7%). The vegetation that obtains the most records of terrestrial mammals was that of the area in the process of restoration. Among the recorded species, one species is considered vulnerable and one species is considered threatened with extinction on the IUCN Red List. Today, the study recorded Herpailurus yagouaroundi, a new species to the list of common species in the area. The results attest to the importance of this area as an ecological refuge, helping to provide food and shelter for terrestrial mammals, for the conservation of mammal species in the Atlantic Forest in the interior of the State of São Paulo.
Characterization of terrestrial mammals in a remnant landscape of Semideciduous Seasonal Forest at the Agricultural Sciences Center (CCA – UFSCar), Araras – SP.
Keywords: Monitoramento de fauna; Armadilha fotográfica; Paisagem modificada por humanos; Fauna monitoring; Trap camera; Landscape modified by humans; CIENCIAS BIOLOGICAS::ZOOLOGIA